Pengaruh Partner Characteristics terhadap Relationship Capital: Studi Empiris Pasca Penggabungan Perusahaan - Muafi, Muafi (BISMA (Bisnis dan Manajemen), 2018)
This study examines if partner characteristics will affect the relationship capital and using data from the Indonesiaan state-owned company that has recently been merged with other stated owned companies. This study devises a multifaceted model based on three constructs of partner characteristics, namely interdependence, cultural compatibility and relative influence, and tests their effects on relationship capital, including reciprocal commitment. Empirical results indicate that partner characteristics have positive affect to relationship capital (reciprocal commitment).